Post-bariatric surgery-associated inflammatory arthritis: a case series describing clinical and MRI features - Kilic, Jehat; Yamancan, Gulsah; Dogan, Yusuf; Sahin, Sumeyye; Oz, Burak; Karatas, Ahmet; Koca, Suleyman Serdar (Springernature, 2026)
Introduction The development of inflammatory arthritis after bariatric surgery has been sporadically reported, but systematic clinical and imaging descriptions remain limited. Understanding these postoperative inflammatory patterns is crucial, and this study examines the emergence and characteristics of spondyloarthritis following bariatric procedures. Material method We conducted a retrospective case series of patients who developed new-onset inflammatory arthritis after bariatric surgery and were evaluated at a tertiary rheumatology center between 2010 and 2025. Demographic data, pre- and postoperative Body Mass Index (BMI), and the interval between surgery and symptom onset were extracted from hospital records. Laboratory evaluations included measurement of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), as well as serological testing for antinuclear antibody (ANA), rheumatoid factor (RF), anti-cyclic citrullinated peptide antibody (anti-CCP), and human leukocyte antigen B27 (HLA-B27). Clinical features such as inflammatory back pain, enthesitis, dactylitis, psoriasis, uveitis, peripheral arthritis, and gastrointestinal symptoms were recorded. Sacroiliac radiographs and MRI scans were reviewed for sacroiliitis, bone marrow edema, structural lesions, and peripheral inflammatory findings. Treatments after symptom onset were documented. Patients were classified as axial or peripheral spondyloarthritis according to ASAS criteria, and seronegative patients with imaging-negative arthritis were categorized as undifferentiated arthritis. Results We describe the clinical, laboratory, and MRI features of 14 patients who developed inflammatory arthritis following bariatric surgery, highlighting patterns of axial and peripheral involvement. Six patients (42.9%) had axial spondyloarthritis with MRI-confirmed sacroiliitis, and seven (50%) had peripheral spondyloarthritis-four with MRI-confirmed peripheral inflammation, one with HLA-B27-associated arthritis, and two with reactive arthritis following infection. One patient (7.1%) had undifferentiated arthritis despite negative serologic, microbiologic, and imaging evaluations. The mean age was 48.1 +/- 12.3 years, and the mean latency from surgery to symptom onset was 56.7 +/- 31.6 months. Enthesitis (35.7%), dactylitis (42.9%), and inflammatory low back pain (78.6%) were common. All patients had prior NSAID exposure, and 6 required biologic or targeted therapy. Conclusion This case series provides a descriptive overview of inflammatory arthritis phenotypes observed after bariatric surgery and should be regarded as hypothesis-generating, warranting confirmation in larger, controlled studies. Despite substantial postoperative weight loss, a subset developed clinically significant inflammatory disease requiring advanced therapies.
Keywords: Bariatric surgery; Obesity; Spondyloarthritis; HLA-B27 antigen; Arthritis